Ancient Indian Ecology and the Modern Climate Crisis: Forgotten Wisdom for a Warming World (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The contemporary climate crisis is often framed as a scientific, technological or economic challenge, yet at its core it reflects a deeper philosophical and civilizational rupture: humanity’s loss of ecological consciousness. Ancient Indian ecological thought—expressed through the Vedas, Upanishads, epics, Buddhist and Jain traditions, and classical environmental ethics—offered a view of life grounded in interdependence, restraint, and moral responsibility toward nature. This article re-examines that wisdom not as nostalgia but as a conceptual resource for navigating global warming. It argues that ancient Indian thought recognized ecological limits long before modern sustainability discourse emerged, viewing nature as a living, sacred continuum rather than an inert resource. By exploring principles such as ṛta (cosmic order), ahimsa (non-harm), aparigraha (non-possession), lokasaṃgraha (welfare of all), and prithvi dharma (Earth ethics), this study demonstrates how Indian ecological philosophy provides a moral grammar for climate resilience. The article also analyses how industrial modernity’s extractive worldview diverges from these insights, resulting in accelerated ecological collapse. By placing ancient Indian ideas in dialogue with contemporary climate science, environmental justice debates, and global policy failures, the paper shows how this wisdom can enrich climate ethics, inspire alternative development models, and offer a deeply human orientation to planetary survival. The conclusion suggests that the climate crisis is not merely an environmental failure but a civilizational amnesia—and recovering ancient Indian ecological sensibilities may illuminate pathways toward a more sustainable future.